Transcriptomic and metabolomic analyses reveal the mechanism of uniconazole inducing hypocotyl dwarfing by suppressing BrbZIP39–BrPAL4 module mediating lignin biosynthesis in flowering Chinese cabbage - Zhang, Liang; Zhong, Min; Yue, Lingqi; Chai, Xirong; Zhao, Puyan; Kang, Yunyan; Yang, Xian (Frontiers in Plant Science, 2022)
Uniconazole, a triazole plant growth regulator, is widely used to regulate plant height and prevent overgrowth of seedlings. However, the underlying molecular mechanism of uniconazole inhibiting hypocotyl elongation of seedling is still largely unclear, and there has been little research on the integration of transcriptomic and metabolomic data to investigate the mechanisms of hypocotyl elongation. Herein, we observed that the hypocotyl elongation of flowering Chinese cabbage seedings was significantly inhibited by uniconazole. Interestingly, based on combined transcriptome and metabolome analyses, we found that “Phenylpropanoid biosynthesis” pathway was significantly affected by uniconazole. In this pathway, only one member of the portal enzyme gene family, named BrPAL4, was remarkably down-regulated, which was related to lignin biosynthesis. Furthermore, the yeast one-hybrid and dual-luciferase assays showed that BrbZIP39 could directly bind to the promoter region of BrPAL4 and activate its transcript. Virus-induced gene silencing (VIGS) system further demonstrated that BrbZIP39 could positively regulate hypocotyl elongation and lignin biosynthesis of hypocotyl. Our findings provide a novel insight into the molecular regulatory mechanism of uniconazole inhibiting hypocotyl elongation in flowering Chinese cabbage, and confirm for the first time that uniconazole decreases lignin content through repressing BrbZIP39-BrPAL4 module mediated phenylpropanoid biosynthesis, which lead to the hypocotyl dwarfing of flowering Chinese cabbage seedlings.